Case studies of fifteen novel species successfully aided with the use of a veterinary teletriage service - Ireifej, Shadi J.; Krol, Justin (Frontiers in Veterinary Science, 2023)
The veterinary medical field is a constantly growing and evolving landscape. Embracing the growth of readily available video conferencing, and potentially spurred by events such as the COVID-19 pandemic causing the public to seek alternatives for medical advice to physical contact at their local veterinary clinic, the use of long-distance advice or telehealth is a rapidly developing field in its own right. In addition to the everyday difficulty of accessing rapid medical care in recent years, there are households with underserved animal groups such as exotics (small mammals, reptiles, birds, fish, etc.), found wildlife, and in some areas of the country, large animals (horses, cows, etc.). Here we present case studies using a teletriage service, VetTriage, to provide health care advice to clients with underserved species including presenting complications, actions taken during the session, medical advice given, and follow up of the case when possible.